Liberty Bar - Simenon, Georges (Inspector Maigret.)
"Maigret is dazzled by Côte d'Azur, but behind the perfect fac̜ade of sun-drenched villas, palm-lined promenades and luxury cars, he discovers the dark reality of a man who can't escape his past any more." -- back cover